Implicações da pandemia de COVID-19 nos aspectos psicossociais e na capacidade para o trabalho em trabalhadores brasileiros - estudo longitudinal - Andrade, Marcela Alves (Universidade Federal de São Carlos, 2024)
The COVID-19 pandemic has raised numerous concerns. Informal workers had to stop working, reducing family income. Workers in essential sectors continued to work. Others, who were able to work from home, faced inadequate working conditions. Objective: To evaluate the psychosocial aspects and work ability of Brazilian workers from different economic sectors, with longitudinal monitoring for 12 months. Methods: Cohort study called “Implications of the Covid-19 Pandemic on Psychosocial Aspects and Work Ability of Brazilian Workers (IMPPAC)” with prospective longitudinal monitoring, with initial and quarterly assessments for 12 months. In the first and last assessment, three instruments were used: 1. Sociodemographic and occupational questionnaire; 2. Copenhagen Psychosocial Questionnaire II (COPSOQ II-Br) short version; and 3. Work Ability Index (WAI). The quarterly assessment involved aspects related to health and work ability. Workers who responded to the initial collection of study 1 were selected. Workers who responded to the baseline and last follow-up were selected for the data that would make up study 2. Results: Study 1: 1,211 workers participated in the research, 52% women, average age 37.7 years, 37% worked in education. The COPSOQ II-Br presented a risk for stress, burnout and work-family conflict; 75% indicated good/excellent work ability. Study 2: In the first wave of the pandemic, remote workers reported more quantitative demands and work-family conflicts, while in-person workers reported more emotional demands, low development of new skills, low commitment, low predictability, low recognition and low satisfaction. They also reported greater instances of offensive behavior. In the second wave, the remote group continued to report high work-family conflict, while the in-person group reported – in addition to the results from the 1st wave – low influence at work, low quality of leadership and burnout. No significant difference was found between the groups in relation to WAI in any of the waves (1st wave: P=0.46; 2nd wave: P=0.62). The majority of workers in both groups reported good work ability in both periods. No difference was found between the groups in relation to the prevalence of mental health problems, except for the prevalence of insomnia in the 12-month follow-up, with higher rates in the remote work group (P=0.03). The infection rate was significantly lower for remote workers (11%) compared to in-person workers (17%). Conclusion: Psychosocial factors and mental health were impacted by the pandemic.
Implications of the COVID-19 pandemic on psychosocial aspects and work ability of brazilian workers - cohort study
Keywords: COVID-19; Impacto psicossocial; Saúde ocupacional; Teletrabalho; Carga de trabalho; Psychosocial aspects; Occupational health; Teleworking; Workload; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL